2019
DOI: 10.14444/6048
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Chronic Irreducible Atlantoaxial Rotatory Fixation in Adults: Review of the Literature, With Two New Examples

Abstract: Atlantoaxial rotatory fixation (AARF) is a rare condition in adults and is almost always due to an accompanying trauma. The first example of traumatic AARF in adults was reported by Corner in 1907 and since then only 55 adult cases with this rare traumatic scenario have been published so far. Approximately 80% of adults with traumatic AARF are diagnosed soon after the traumatic events. However, in the remaining casualties, the condition might be missed with some delay from the diagnosis to treatment. If this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Treatment strategies for a case diagnosed early generally involve a closed reduction and immobilization with a halo-ring or cervical collar. For cases refractory to this treatment, as is common in chronic or recurrent cases with a delayed diagnosis, surgery may be indicated [2 , 5] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment strategies for a case diagnosed early generally involve a closed reduction and immobilization with a halo-ring or cervical collar. For cases refractory to this treatment, as is common in chronic or recurrent cases with a delayed diagnosis, surgery may be indicated [2 , 5] .…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine injuries occur in 2.4% of blunt traumas [1] . Atlantoaxial rotatory subluxation (AARS) is a rare outcome of trauma in adults [2] . As reported by Rahimizadeh et al in 2010, in the 20th century, there were only 57 adults with reported cases of atlantoaxial rotatory fixation, a term that encompasses rotatory displacement arising from either subluxation or dislocation [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atlantoaxial rotatory fixation (AARF) is an acquired fixed rotation abnormality of the C1 vertebra on C2 that impedes turning of the neck and typically manifests with painful torticollis. It is primarily a condition of childhood although adolescent and adult cases are seen [ 1 3 ]. Clinical diagnosis of AARF is suspected on the basis of a fixed rotational deformity of the neck, often with the typical “Cock-Robin” position created by cervical lateral flexion, forward flexion and rotation [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is typically seen in childhood, with adolescent and adult cases occurring rarely. [1][2][3] Clinical diagnosis of AARF is based on fixed rotational deformity of the cervical spine with the head held in a "cock-robin" position with rotation and forward and lateral flexion. 1,4,5 Without treatment, the atlantoaxial joint is at risk of fusion in the abnormal position, which can cause cosmetic effects, facial asymmetry, functional disability, chronic pain, and compensatory deformity in the subaxial spine.…”
mentioning
confidence: 99%